Aplikasi Pendeteksi Plagiasi pada Universitas Indo Global Mandiri Berbasis Web - Dhamayanti Dhamayanti; Lidia Permata Sari (Jurnal Informatika Global)
ABSTRACTThesis is a final project that must be taken by students to complete their studies at the Indo Global Mandiri University in Palembang. Thesis data processing and storage, especially in the Information Systems department is still done conventionally, so checking the similarity of the title even the contents of the student thesis is difficult to detect. Difficulties in detecting the title and content of the thesis cause students to easily and freely plagiarize the proposal preparation and thesis report from beginning to end without being known by the lecturer and the Information System department. Plagiarism is the act of a shortcut that steals ideas, takes the work, and recognizes the work of others as their own without including references from the original source. This research will discuss the problem of plagiarism in the Information Systems department through making applications that can detect the plagiarism of titles and contents of the thesis especially in the information systems department so as to overcome the plagiarism problems faced by the information systems department. This plagiarism detection application is built using the cosine similarity method. Cosine similarity is a method for calculating similarity (level of similarity) between two object. In testing the similarity of documents with the results of the study, cosine similarity has a higher degree of accuracy. Cosine similarity is used to calculate the similarity value by equating said words and become one of the techniques to measure the similarity of popular texts. Plagiarism detection application using cosine similarity method which is implemented with PHP and MySQL as the database can help efforts to reduce the occurrence of plagiarism in the title and contents of the thesis in the Information Systems department.  Keywords : Plagiarism, Plagiarism Detection Application, Cosine Similarity, PHPABSTRAKSkripsi merupakan tugas akhir yang wajib ditempuh mahasiswa untuk menyelesaikan studi di Universitas Indo Global Mandiri Palembang. Pengolahan dan penyimpanan data skripsi  khususnya pada program studi Sistem Informasi masih dilakukan secara konvensional, sehingga pengecekan kemiripan judul bahkan isi skripsi mahasiswa sulit untuk dideteksi. Kesulitan pendeteksian judul dan isi skripsi menyebabkan mahasiswa dengan mudah dan bebas melakukan plagiasi pada pembuatan proposal maupun laporan skripsi dari awal hingga akhir tanpa diketahui oleh dosen dan pihak program studi. Plagiasi merupakan tindakan sebuah jalan pintas yang mencuri ide, mengambil hasil karya, dan mengakui hasil karya orang lain sebagai miliknya sendiri tanpa mencantumkan referensi dari sumber aslinya. Penelitian ini akan membahas permasalahan plagiasi pada program studi Sistem Informasi melalui pembuatan aplikasi yang dapat mendeteksi plagiasi judul dan isi skripsi khusunya pada program studi sistem informasi sehingga dapat mengatasi permasalahan plagiasi yang dihadapi oleh program studi sistem informasi. Aplikasi pendeteksi plagiasi ini dibagun  dengan menggunakan metode cosine similarity. Cosine similarity adalah metode untuk menghitung similarity (tingkat kesamaan) antar dua buah objek. Pada pengujian kesamaan dokumen dengan hasil penelitian menunjukkan cosine similarity memiliki tingkat akurasi yang lebih tinggi. Cosine similarity digunakan untuk menghitung nilai kemiripan dengan menyamakan kata perkata dan menjadi salah satu teknik untuk mengukur kemiripan teks yang popular. Aplikasi pendeteksi plagiasi dengan menggunakan metode cosine similarity yang diimplemntasikan dengan PHP dan MySQL sebagai databasenya dapat membantu upaya mengurangi terjadinya plagisi pada judul dan isi skripsi di program studi Sistem Informasi.Kata kunci : Plagiasi, Aplikasi Pendeteksi Plagiasi, Cosine Similarity, PHP